Application of noise guidance to the assessment of industrial noise with character on residential dwellings in the UK. (June 2015) - Baker, Daniel
Highlights: I critically review the application of noise guidance to industrial noise. I compare four sources of industrial noise with BS8233, WHO 1999 & 2009 and BS4142. Guidance for anonymous noise understates impact when applied to industrial noise. Abstract: British Standards are used to assist the assessment of noise impact from new or existing sources and assist judgements of acoustic acceptability. Standards may include provision for the assessment of noise with character whilst others are limited to anonymous noise. Noise guidance designed for the assessment of anonymous/characterless noise appears increasingly used to justify acceptable noise impact from industrial noise with character (identifiable site noise). The result is an inappropriate comparison with guideline values that ignore noise character and context in the assessment of noise acceptability at dwellings. This technical note conducts a critical review of noise guidance and considers four sources of industrial noise with character. Preliminary comparisons of analysed noise data with the World Health Organization Guidelines for Community Noise (WHO 1999), World Health Organization Night Noise Guidelines for Europe (WHO 2009), BS8233 2014 Guidance on sound insulation and noise reduction for buildings (BS8233) and BS4142 2014 Methods for rating and assessing industrial and commercial sound (BS4142) demonstrate guidance designed for anonymous noise significantly understates the impact of industrial noise with character on dwellings when compared to noise guidance for rating and assessing industrial sound accompanied with context based observations of noise impact.